The Association between Helicobacter Pylori Infection and Iron Deficiency Anemia in Children: A Systematic Review and Meta-Analysis - Hamdan, Sara Z.; Hamdan, Hamdan Zaki; Nimieri, Mustafa; Adam, Ishag (Journal of Pediatric Infectious Diseases, 2022)
Objectives This study, comprising a systematic review and meta-analysis, was conducted to assess the association between Helicobacter pylori infection and the risk of iron deficiency anemia (IDA) in children.Methods We followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Relevant published studies were searched in the databases. Retrieved studies were assessed for quality using the Modified Newcastle-Ottawa Scale for quality assessment. The “meta” package of statistical software “R 4.0.3 was used for statistical analysis.Results Overall, 22 eligible studies (eight cross-sectional, six randomized control trials, five case-control, two surveys, and one cohort), including nine (40.9%) from Asia, four (18.1%) from America, four (18.1%) from Africa, four (18.1%) from Europe, and one (4.5%) from Australia with a total of 3,434 cases and 4,455 controls were included in this systematic review and meta-analysis. We found that H. pylori infection was associated with a high risk of IDA (odds ratio 1.70, 95% confidence interval 1.21 − 2.38) in a random-effects model. Meta-regression analysis showed that none of the investigated factors that may affect the prevalence of IDA reached statistical significance. There was statistically significant difference between results when studies were categorized according to the methods used to diagnose H. pylori and level of incomes based on World Bank classification. The GRADEpro Guideline Development Tool evidence for the risk of IDA was of a “moderate certainty.”Conclusions This meta-analysis with a “moderate certainty” of evidence showed an association between H. pylori infection and a high risk of developing IDA in children.
Keywords: breath test; children; H. pylori; iron deficiency anemia; meta-analysis